Effects of Oral Morphine on Dyspnea in Patients with Cancer: Response Rate, Predictive Factors, and Clinically Meaningful Change (CJLSG1101). (18th January 2019) - Takahashi, Kosuke; Kondo, Masashi; Ando, Masahiko; Shiraki, Akira; Nakashima, Harunori; Wakayama, Hisashi; Kataoka, Kensuke; Yamamoto, Masashi; Sugino, Yasuteru; Nishikawa, Mitsunori; Imaizumi, Kazuyoshi; Kojima, Eiji; et al.
Abstract: Background: Although the efficacy of parenteral morphine for alleviating dyspnea has been previously demonstrated in several studies, little is known regarding the efficacy of oral morphine for dyspnea among patients with cancer, including its response rate and predictive factors of effectiveness. Therefore, the aim of this study was to clarify the effectiveness of oral morphine on dyspnea in patients with cancer and elucidate the predictive factors of its effectiveness. Subjects, Materials, and Methods: In this multicenter prospective observational study, we investigated the change in dyspnea intensity in patients with cancer before and after the administration of oral morphine by using a visual analog scale (VAS). We also administered a self‐assessment questionnaire to determine whether the patients believed oral morphine was effective. Results: Eighty patients were enrolled in the study, and 71 of these patients were eligible. The least square mean of the VAS scores for dyspnea intensity was 53.5 at baseline, which decreased significantly to 44.7, 40.8, and 35.0 at 30, 60, and 120 minutes after morphine administration, respectively. Fifty‐four patients (76.1%) reported that oral morphine was effective on the self‐assessment questionnaire. Among the background factors, a high score for "sense of discomfort" on the Cancer Dyspnea Scale (CDS) and a smoking history of fewer pack‐years were associated with greater effectiveness. Conclusion: Oral morphine was effective and feasible for treating cancer‐related dyspnea. A higher score for "sense of discomfort" on the CDS and a smaller cumulative amount of smoking may be predictive factors of the effectiveness of oral morphine. Abstract : Dyspnea is one of the most difficult symptoms to manage in clinical practice. This article evaluates the effectiveness of oral morphine for dyspnea in cancer patients.